Pengaruh Kualitas Pelayanan, Promosi, Dan Kepercayaan Terhadap Loyalitas Konsumen Di Alfamart MT Haryono (Studi Kasus Pada Mahasiswa Manajemen UNISMA Angkatan 18) - Muhammad Salman Farisy; Muhammad Ridwan Basalamah; Rahmawati Rahmawati (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThis study was conducted to determine the effect of service quality, promotion, and trust on consumer loyalty at Alfamart MT Haryono (Case Study on Management Students of UNISMA Class 18). This research belongs to the type of quantitative research, which was conducted to examine the effect between the variables. The population in this study were students of the Faculty of Economics and Business, Management Study Program, Islamic University of Malang in the 2018 Academic Year who had shopped at Alfamart Unit MT.Haryono 3 Dinoyo, Malang City. The sampling technique used in this study used a purposive sampling technique. The criteria for sampling are students who are active in FEB 18 and have shopped at Alfamart MT Haryono. Samples were taken using the Malhotra formula so that 90 samples were obtained. Data analysis in this study consisted of instrument testing, classical assumption test, multiple linear regression analysis, hypothesis testing, and coefficient of determination test. The results of this study indicate that based on the results of the F test and t test there is a simultaneous and partial effect between the variables of promotion, service, and trust on the variable of consumer loyalty. Adjusted R Square of 76.0% to the dependent variable, namely consumer loyalty can be explained by the variables of service quality (X1), promotion (X2), trust (X3) while 24.0% is explained by other variables outside the research model. Keywords: Consumer Loyalty, Service Quality, Promotion, Trust